Russian Experience of Concervation and Renowation of Industrial Regions’ Heritage - ZAYTSEVA, Anna; BREL, Olga; KAIZER, Philipp (Journal of Environmental Management and Tourism; Vol 9 No 4 (2018): JEMT Volume IX Issue 4(28) Summer 2018, 2018)
The socio-economic development of the society caused the emergence of large-scale industrial areas in city centers around the world. Thanks to the industrial revolution, industrial facilities have been closely intertwined in the urban structure. The article discusses the problem of conservation and renovation of Russian industrial regions’ heritage. A significant experience in renovating former industrial facilities has been accumulated in the world. The authors demonstrate the ways of industrial heritage conservation and renovation both in the world and in Russia. And they try to reveal the conditions for development of industrial tourism in Russia.